LEGISLATIVE READINESS FOR DIGITAL REALITY: TOKENIZATION IN SERBIAN LEGISLATION - Nikolić, Ljubica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The paper analyzes the legal framework of tokenization in the Republic of Serbia, with a focus on digital tokens as a specific form of digital assets, defined by the Law on Digital Assets. The paper points out the basic types of tokens, as well as the challenges of their legal qualification, especially in terms of separation from virtual currencies and determining whether they have the characteristics of financial instruments. The legal regulation related to the tokenization of securities and real estate is also analyzed, with a special focus on the technological limitations of the application of DLT (distributed ledger technology) within the framework of existing institutional mechanisms. The paper points out the lack of precise criteria for the classification of tokens in Serbian law, as well as the need for clearer and more encouraging guidelines. The aim of this paper is to point out the need to improve existing legislation in order to ensure greater legal certainty, encourage innovation, and enable wider acceptance of tokenization in the Republic of Serbia.
Keywords: digital tokens; tokenization; Digital Assets Act; effects of implementing legal provisions